A reply to my critics - Broome, J (Wiley, 2016)
'Climate Matters' is aimed at a wide readership. When I was commissioned to write the book, I thought that people would be interested in what moral philosophy has to say about the private morality of climate change. How should we as individuals respond to the existence of climate change? I had not previously thought much about this question, but I drew my own conclusions about it and presented them. I surprised myself by the conclusions I came to.